2018
DOI: 10.1186/s12891-018-2080-0
|View full text |Cite
|
Sign up to set email alerts
|

Range of motion after total knee arthroplasty in hemophilic arthropathy

Abstract: BackgroundOutcomes of total knee replacement in cases of hemophilic patients are worse than in patients who undergo operations due to osteoarthritis. Previous publications have reported varying rates of complications in hemophilic patients, such as infection and an unsatisfactory range of motion, which have influenced the survival of prostheses. Our retrospective study evaluated the data of hemophilic patients regarding changes in the development of the range of motion.MethodsThe data and clinical outcomes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Goddard et al reported the range of flexion and flexion contracture improved from 68° to 79° and 9.6° to 4.7°, respectively (62). Similar results were published by Kubes et al and Silva et al where TKA surgery decreased the average flexion contracture from 17° to 7° and 18° to 8° and improved the average preoperative flexion range from 73° to 80° and 59° to 75°, respectively (35,63). Finally, a meta-analysis by Moore et al showed an average decrease of 9.7° in flexion contracture and an increase 15° in flexion after TKA surgery (53).…”
Section: Range Of Motionsupporting
confidence: 67%
See 2 more Smart Citations
“…Goddard et al reported the range of flexion and flexion contracture improved from 68° to 79° and 9.6° to 4.7°, respectively (62). Similar results were published by Kubes et al and Silva et al where TKA surgery decreased the average flexion contracture from 17° to 7° and 18° to 8° and improved the average preoperative flexion range from 73° to 80° and 59° to 75°, respectively (35,63). Finally, a meta-analysis by Moore et al showed an average decrease of 9.7° in flexion contracture and an increase 15° in flexion after TKA surgery (53).…”
Section: Range Of Motionsupporting
confidence: 67%
“…The prevalence of PJI in the non-hemophilic population is around 1% (85,86). However, most studies have shown significantly higher rates of PJI in PWH with prevalence ranging from 5% to 17% (21,35,66,67). The reason behind the increased infection rate in the hemophilic population is still unknown (72); nevertheless, there are several explanations that have been proposed including poor skin condition caused by coagulation factor administration, immunosuppression, bacteremia from contamination during repeated intravenous self-administration of coagulation factor concentrate, increased incidence of postoperative hematoma or concomitant HIV or HCV infection (53,87).…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, functional outcomes of TKR in hemophilic patients have also shown suboptimal improvement in motion. The surgery was reported to have little effect on the flexion of the knee but reduced flexion contracture, which overall seemed to improve the ROM 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Kubes et al. [ 30 ] reported that hemophilic patients should be operated before the preoperative flexion contracture reaches 22° to obtain a contracture < 15° postoperatively or before the preoperative contracture reaches 12° to obtain a contracture < 5°. In HA, repeated intraarticular bleeding occurs with subsequent intraarticular deposition of hemosiderin and iron, which leads to upregulation of proinflammatory cytokines and, consequently, synovial hypertrophy and articular destruction [ 31 ].…”
Section: Discussionmentioning
confidence: 99%